The effect of web 2.0 based technology applications on speaking skills and speaking anxiety in teaching Turkish as a foreign language: Voki example - Aktaş, Elif (Frontiers in Psychology, 2023)
The aim of this study is to examine the effect of Voki, one of the web 2.0-based technology applications, on Turkish learners’ speaking skills and speaking anxiety. In the study, exploratory sequential design, one of the mixed design types in which quantitative and qualitative approaches are used together, was adopted. The study group of the research consisted of 61 students at A2 level (31 experimental group, 30 control group) who learn Turkish as a foreign language at the Turkish Language Teaching Center of a university located in the south of Turkey. Speaking Anxiety Scale and Speaking Skill Assessment Form were used as data collection tools. During the 6-week intervention, the experimental group used Voki in speaking lessons, while the control group did not use any technology-based web 2.0 tool. Descriptive statistics, chi-square analysis, dependent and independent groups t-test were used to analyze the quantitative data collected in the study. Descriptive analysis and content analysis were used to analyze the qualitative data collected through a semi-structured interview form. As a result of the study, it was determined that the Voki application improved the speaking skills of the students in the experimental group and reduced their speaking anxiety. It was also determined that the students in the experimental group expressed positive opinions about the application. Therefore, the use of Voki application in speaking activities in foreign language teaching is recommended.